KEARIFAN LOKAL DALAM PENGELOLAAN HUTAN (STUDI KASUS KELEMBAGAAN SASI HUTAN DI DESA KAILOLO KECAMATAN PULAU HARUKU KABUPATEN MALUKU TENGAH) - Husain Marasabessy (JURNAL HUTAN PULAU-PULAU KECIL, 2018)
This study aims to determine the role of local Sasi institutions in forest management activities, which can be used in formulating forms of forest management based on regional characteristics in realizing sustainable forest management and improving community welfare. Data collection is done by observing all community activities both in the forest and in residential areas. Interviews are conducted with all stakeholders to obtain systematic and intensive data and information including village government, managers (kewang), youth and student leaders, academics, NGOs and documentation studies in the form of library studies and photographs relating to research. The results of the study show that sasi is a form of temporary prohibition on the community to refrain from exploiting natural resources that are on land that are privately owned (non-communal) or collectively (communal rights) and at sea owned by the management agency (Kewang). Sasi law for teresterial land (forest) has management stages, namely planning, implementation, supervision, yield management, and marketing. Government policies in the forestry sector such as the forestry law number 41 of 1999 year concerning forestry, and the decision of the minister of forestry number 31 of 2001 year concerning social law are seen to be in line with the sasi law. In its development, sasi as a model of local wisdom in Moluccas Province faced obstacles in its implementation, both those who came from outside and inside the community, such as the proportion of forest area with the number of members of the community, conflicts between customary law and national law, and government policies in the form of HPH which is a threat to the territory of the country.